A rapid assay for measuring the activity and the Mg2+ and Ca2+ requirements of phosphatidate phosphohydrolase in cytosolic and microsomal fractions of rat liver. - Martin, A (1987)
1. A rapid extraction and purification scheme was designed for the recovery of [3H]diacylglycerol formed during the assay of phosphatidate phosphohydrolase. 2. The importance of removing polyvalent cations, particularly Ca2+, from the phosphatidate and other reagents used in the assay of the phosphohydrolase activity was demonstrated. This was achieved mainly by treating the phosphatidate with a chelating resin and by adding 1 mM-EGTA and 1 mM-EDTA to the assays. 3. The activity of the phosphohydrolase in dialysed samples of the soluble and microsomal fractions of rat liver was very low. 4. Addition of optimum concentrations of MgCl2 resulted in a 110-167-fold stimulation in activity. 5. CaCl2 was also able to stimulate phosphohydrolase activity, but to a much smaller extent than MgCl2. 6. Chlorpromazine, an amphiphilic cation, inhibited the reaction when it was measured in these experiments by using a mixed emulsion of phosphatidylcholine and phosphatidate at pH 7.4. 7. Microsomal fractions that were preincubated with albumin contained very low activities of the Mg2+-dependent phosphohydrolase. When these were then incubated with the soluble fraction in the presence of oleate, the soluble phosphohydrolase attached to the microsomal membranes, and it retained its high dependency on Mg2+.